Investigation of herbicide resistance in Japanese brome (Bromus japonicus) and responses of grain sorghum (Sorghum bicolor), & corn (Zea mays) to multiple herbicides at high-temperature stress - Adari, Manogna Devi (Kansas State University, 2024)
Weed infestation poses a significant challenge to crop production. Post-emergence (POST) herbicides are commonly used to control weeds in crops including, wheat (Triticum aestivum L.), sorghum (Sorghum bicolor L. Moech), and maize or corn (Zea mays L.). Unfortunately, an inevitable consequence of the repeated and indiscriminate use of herbicides is the evolution of herbicide resistance in weeds. In the US, recently the first case of resistance to POST-applied acetolactate synthase (ALS)-inhibitor herbicides was found in Japanese brome (Bromus japonicus Thumb.), a problem weed in winter wheat (focus of Chapter 2). Although POST herbicides are excellent options for weed control, some of these herbicides are also known to cause crop injury, when exposed to abiotic stresses such as high-temperature (heat) stress, which was investigated in sorghum and corn (Chapters 3 and 4). The objectives of this thesis were to 1) confirm and characterize the ALS-inhibitor resistance in Japanese brome; 2) assess the response of grain sorghum to POST herbicides under high-temperature stress; and 3) evaluate corn response to POST herbicides under high-temperature stress. Experiments were conducted either in the greenhouse or in controlled environmental growth chambers. In objective 1, the level of resistance and mechanism of resistance to ALS-inhibitors were investigated in three Japanese brome populations, R1, R2 and R3. Results indicate ~ 167-, ~ 125-, and ~ 667-fold resistance to ALS-inhibitor, propoxycarbazone-Na in R1, R2, and R3, respectively, compared to a susceptible population. Additionally, mutations in the ALS gene resulting in amino acid substitutions i.e., Proline-197-Threonine in R3, R1 and Proline-197-Serine in R2, R1 were identified. The resistant populations also exhibited cross-resistance to other ALS-inhibitors, such as sulfosulfuron, mesosulfuron, pyroxsulam, and imazamox. Cross resistance to imazamox possibly via cytochrome P450 enzyme mediated metabolism was also found in R3 population. To achieve objective 2, grain sorghum genotypes, RTx430 and P84G62, were selected and grown in growth chambers maintained at two temperature regimes: optimum (OT: 32/22 °C; day/night (d/n)) and high-temperature (HT: 40/30 °C; d/n) and were treated separately with herbicides, e.g., 2,4-D, pyrasulfotole + bromoxynil, or mesotrione. Results revealed that at HT, grain sorghum is prone to more herbicide injury when treated with mesotrione or pyrasulfotole + bromoxynil but not with 2,4-D. Additionally, P84G62 had less injury compared to RTx430, irrespective of temperature or herbicide treatments. In objective 3, a similar experimental procedure was used, and corn genotype DKC59-82RIB, plants were grown at OT (30/25 °C; d/n) and HT (40/35 °C; d/n) and treated separately with 2,4-D, dicamba, mesotrione, tembotrione, or atrazine. The results indicate that at HT, corn plants exhibit more injury when treated with the above herbicides than at OT. Overall, the outcome of this research confirms alterations in the target site of ALS-inhibitors bestow resistance in Japanese brome. More importantly, the results also highlight that under HT stress, grain sorghum and corn are prone to POST-applied herbicide injury. These findings emphasize the necessity of sustainable weed management strategies amidst challenges like evolving herbicide resistance and changing climate conditions.
Keywords: Herbicide resistance; Japanese brome; Grain sorghum and corn; Acetolactate Synthase (ALS)-inhibitors; High-temperature stress; POST herbicides